Determination of precise geodetic coordinate using global navigation satellite system (GNSS) precise point positioning method - Abdul Rashid, Fauziah (2015)
Presently the Precise Point Positioning (PPP) enables users to dual-frequency GNSS positioning at the decimetre/centimetres in kinematic mode using static and/orbit of the satellite. PPP has the ability to determine position in rural areas far from GNSS reference stations that do not have network RTK. This study aimed to examine the suitability of the PPP as an alternative to RTK network using VRS method. The existing GNSS reference station that is ARAU, GETI, CAME, KLAW, JUML and LAB1 used in this study. The selection of reference GNSS stations based on geographic distribution and weather conditions at the time. Data collection at the reference stations is the Trimble GPS 5700, Trimble NetR5 and Trimble NetR9 GNSS system. The data observed for 24 hours a day with 30 seconds interval for three consecutive days were used for this project. For the purposes of the data processing, WayPoint GrafNav 6.0 software used. Overall, the objective of this project was accomplished. Based on the analysis, the coordinate difference ±2cm for northing, and easting ±2cm also for height ±6cm. The value of accuracy are allowed as statedin the circular Department Survey and Mapping Malaysia volume 6/2009. The results from this study can be used as a benchmark to see the accuracy of Precise Point Positioning method compared to the existing VRS network correction method for cadastral and mapping purposes.